Deconstructing the EU General Data Protection Regulation - Rong WANG (大数据)
The EU General Data Protection Regulation (GDPR) has taken effect on May 25,2018.In order to catch up with the new trend of digital era,companies from all over the world are actively preparing for the related compliance work.The major changes of this new regulation were demonstrated comprehensively.It will provide a reference for companies and new prospective for China’s data protection policy making in big data era.